Rape and genital maiming/mutilation as a torture method in Ethiopian Prisons: Evidence that prisoners of conscience, critical journalists, and activists have been abused - Berhanu, Girma (Advances in Social Sciences Research Journal, 2018)
In recent years, it has come to be recognized that men and women activists, prisoners of conscience, and critical journalists in Ethiopia have been sexually abused in detention as a method of torture. We do not know exactly how common the abuse is. Few former prisoners are willing to disclose their experience. Rape, genital maiming/mutilation, and sexual violence including sodomy are under-reported by both men and women. Male survivors of sexual violence are less likely than women and girls to disclose assaults (Callender & Dartnall 2011)[1] due to a combination of cultural and religious reasons manifested through shame, confusion, and guilt. This study uses personal accounts and anecdotal evidence to investigate the alleged abuses. The data indicate that genital maiming/mutilation and rape have been practiced in an attempt to silence dissent and humiliate the victims. This study highlights the urgent need for the international community and local human rights organizations to address seriously the needs of victims of sexual violence such as genital maiming, rape, and other obscene and sadistic, ill treatment in prisons. The human cost of the silencing and the marginalization of survivors can only be estimated at present. [1]Callender, T. and E. Dartnall (2011) "Mental health responses for victims of sexual violence and rape in resource poor settings." SVRI Briefing Paper, Sexual Violence Research Initiative, Medical Research Council, Pretoria, South Africa (e-version).